Nepal - Towards a Sustainable Approach for Poverty Reduction and Decentralization : A Note on Nepal's Proposed Poverty Alleviation Fund - World Bank (Washington, DC, 2013)
The objective of this policy note, is to provide advice to the Government of Nepal on the best approach to adopt for the proposed Poverty Alleviation Fund (PAF) to adequately address the problems related to poverty reduction, and service improvement in remote areas. The report first presents an overview of the conceptual framework for analysis, focusing attention on the particularly important aspects of poverty - risk and vulnerability - to then provide insights on the understanding of the nature of poverty in the country, and how to address it. It specifies that risk management, if properly implemented, can induce economic growth, leading to a longer term sustained reduction in poverty, while decentralization empowers local communities, by addressing government's failures in delivering services in areas critical to poverty reduction. The report further reviews the experience of development projects in Nepal, through a sector wide approach, where findings suggest that community-based models of investment, and service delivery, perform better than central agency models, underlining high levels of community participation and good cost effectiveness. Nonetheless, upon examining micro-finance, and despite the country's vibrant micro-finance sector, the report questions its outreach, and coverage to the rural poor, which has remained low. The successful implementation of the PAF lies in its potential to assist in Nepal's decentralization program, and, its effectiveness in addressing risk, vulnerability, and poverty. But without external support, PAF is not likely to materialize due to financing, and management constraints.